2002
DOI: 10.1002/er.819
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy controlled central heating system

Abstract: SUMMARYIn this paper a comparison study was carried out in order to understand how two different systems, classical and fuzzy logic control of central heating affect the economy and comfort of private homes or offices. Also a literature review was done to help decide which one of these systems is more effective. The objective of the fuzzy controller heating system is to estimate the actual heat requirement of the house. It uses a total of five inputs, four of which are derived from energy consumption curve, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…refs. [10][11][12][13][14][15][16][17][18][19] and the references therein). In particular, significant attention has been given to the modeling, construction and optimization of core components of central heating system, such as pipe networks and piping elements, radiators and other heating systems, boilers, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…refs. [10][11][12][13][14][15][16][17][18][19] and the references therein). In particular, significant attention has been given to the modeling, construction and optimization of core components of central heating system, such as pipe networks and piping elements, radiators and other heating systems, boilers, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, significant attention has been given to the modeling, construction and optimization of core components of central heating system, such as pipe networks and piping elements, radiators and other heating systems, boilers, etc. Furthermore, different control techniques have been applied to such systems in order to regulate temperature in heated areas, including classical and metaheuristic PID controllers [13−15] , fuzzy control schemes [16] , adaptive controllers [19] , optimal controllers [17] , etc.…”
Section: Introductionmentioning
confidence: 99%
“…Mendi et al . carried out to understand how two different systems, classical, and fuzzy logic control of central heating affect the economy and comfort of private homes or offices. It was shown that the fuzzy controlled heating system was more effective, also it maximized the economy and the comfort of the consumer.…”
Section: Introductionmentioning
confidence: 99%
“…This system is composed of a smart card unit that acts as a user machine interface as well as sensors, actuators, interfaces, a PLC controller (including the fuzzy control algorithm), local operating network modules and devices, and an optimal PC to monitor the system performance. Mendi et al [16] carried out to understand how two different systems, classical, and fuzzy logic control of central heating affect the economy and comfort of private homes or offices. It was shown that the fuzzy controlled heating system was more effective, also it maximized the economy and the comfort of the consumer.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of modelling and control of central heating systems has attracted considerable attention during the last years (see Cai, 2006;Hansen, 1997;Koumboulis et al, 2007;Koumboulis et al, 2008a and b;Koumboulis et al, 2009a,b and c;Koumboulis and Kouvakas, 2010;Mendi et al, 2002;Morel et al, 2001;Zaheer-Uddin et al, 1994;Zanobini et al, 1998 and the references therein). Significant attention has also been given to the modelling of core components of central heating systems as well as to the application of different control techniques to regulate the performance variables.…”
Section: Introductionmentioning
confidence: 99%